Econazole depleted calcium release-activated calcium (CRAC) current through blockade of voltage-dependent Ca 2+ channels - Agung Endro Nugroho; Hari Purnomo; Kazutaka Maeyama (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Econazole is an azole antifungal agent which can block the calcium release-activated calcium (CRAC) current in human leukaemic T cell line. The phenomenon is also possible to occur in mast cell such as RBL-2H3 (rat basophilic leukemia) cells, a tumor analog of mast cells. In the study, we investigated effect of econazole on 45Ca2+ uptake into the cells in response to thapsigargin, an ATP-dependent Ca2+ (SERCA) inhibitor, by direct measurement of radiolabelled Ca2+ uptake in cells. The mechanism underlying this effect of econazole was studied using molecular modelling. In present study, econazole inhibited 45Ca2+ influx into mast cells in absence of mast cells inducer, thapsigargin. Moreover, econazole potently suppressed the 45Ca2+ influx induced by thapsigargin. It was supported that econazole also inhibited Ca2+-induced tracheal contraction. The increase of Ca2+ was stimulated by the opening of voltage-dependent Ca2+ channels activated by KCl-induced membrane depolarization. Based on molecular docking study, score of interaction (equal to energy of interaction) of 3FGO, a main protein target on Ca2+ -ATPase, with native ligan, thapsigargin and econazole were -76.941, -117.205, and -92.277, respectively. The interaction of thapsigargin and Ca2+ -ATPase was more stable than this of econazole and Ca2+ -ATPase. It suggests that it would be difficult for econazole to block the interaction of thapsigargin with Ca2+ -ATPase to increase intracellular Ca2+.In conclusion, econazole inhibited the increase of intracellular Ca2+involving the blokade of voltage-dependent Ca2+ channels, but not involving the Ca2+ -ATPase pathway.Key words :econazole, Ca2+ -ATPase, CRAC current, thapsigargin